Преса як засіб національної самоідентифікації в умовах мультикультурного суспільства Буковини кінця ХІХ – початку ХХ століть - Hrynivskyi, Taras; Paziuk, Roman (WYDAWNICTWO UNIWERSYTETU RZESZOWSKIEGO, 2021)
The article reviews the Bukovinian press at the turn of the 19th and 20th centuries. The subject of the analysis is the periodicals of various nationalities (in Ukrainian, German, Romanian and Polish), promoting the ideas of national identity and the consolidation of the population in the conditions of the coexistence of many cultures. The history of journalism and printing in Bukovina covers a period of over two centuries, which consists of successive stages of rapid development, numerous transformations, and finally decay. In its long duration it contributed to the development of the multinational culture of this land; the then press and books are characterized by linguistic polyphony, there are publications in German, Ukrainian (Ruthenian, Ruthenian), Romanian, Polish and Yiddish. Numerous publishing houses and printing houses had multilingual projects to their credit, for example, it happened that one title was published simultaneously in several language versions. The Austro-Hungarian period was exceptionally favorable for such initiatives, as the empire pursued a policy of tolerance and democracy towards the peoples inhabiting its territory. The legacy of this time, although quite extensive, has not yet been fully explored. Although there are works on the history of the press and books of specific nationalities, there is still no comprehensive analysis that would include multilingual publishing production. Therefore, the main aim of the article was a statistical comparison and analysis of the multilingual Bukovinian press in the context of the growth of national identity and educational movements of national societies at the turn of the 19th and 20th centuries. The research aims to: define the role of national and educational societies in Bukovina in the process of shaping the national identity of the local population; the selection of periodicals that acted as organs of various national and international ideas; general characteristics of the ideas, topics and types of the most famous publications in different languages in the light of their educational role. The subject and subject literature included multilingual publications from the indicated period, memories of participants in national movements, as well as research by contemporary and contemporary scientists on the history of the Bukovinian press and the general history of printing.
Press as a means of national self-identification under conditions of multicultural society of Bukovyna at the end of the 19th – at the beginning of the 20th century
Keywords: історія журналістики, друкарствo, часописи, преса Буковини.; history of journalism, history of printing, periodicals, Bukowina press.